Code Mixing in Episode 4 - Blind Audition “The Voice Indonesia 2019” - Sri Rahayu; Hotni Rambe (English Education : English Journal for Teaching and Learning, 2022)
The purpose of this research was to know the types of code mixing that used in episode 4–blind audition “The Voice Indonesia 2019”. The researcher used four videos as data from youtube channel. This research used library research.  The data analysis used the following steps: organize and prepare the data for analysis, watching the videos in many times, coding the data use coding process to generate a description and give the description of the data findings. The result was found there are 87 data that contains code mixing. From 87 data of code mixing that found by the researcher, there are 72 data that include to intra sentencial code mixing, 8 data include to intra lexical code mixing, and 7 data include to involving a change pronounciation. The dominant code mixing was intra sentencial code mixing.